Highly thermostable extracellular lipase-producing Bacillus strain isolated from a Malaysian hotspring and identified using 16S rRNA gene sequencing - Akanbi, Taiwo Olusesan; Kamaruzaman, Azura Liana; Abu Bakar, Fatimah; Sheikh Abdul Hamid, Nazimah; Radu, Son; Abdul Manap, Mohd Yazid; Saari, Nazamid (Faculty of Food Science and Technology, Universiti Putra Malaysia, 2010)
The activities of lipase produced by five lipases-producing thermophilic bacteria strains (SY1, SY5, SY6, SY7 and SY9) isolated from Selayang Hot Spring in the western part of Peninsular Malaysia were analyzed and compared. SY7 and SY9 had considerably higher lipolytic activities than those of SY1, SY5 and SY6. Thermostabilities of lipase produced by all strains were determined after heating at 80°C for 30 minutes. Strain SY7 retained the highest lipolytic activity of 77%, while others had infinitesimally low thermostability (retaining less than 34% of their original activity) at the same temperature and time. SY7 was chosen for further characterization because it showed exceptionally high lipase activity and thermostability. It was identified as belonging to Bacillus species by the conventional Gram-staining technique, Biochemical tests and Biolog Microstation system. By using 16S rRNA gene sequencing, strain SY7 generated the same expected PCR product with molecular weight of 1500 base pair. It displayed 98% sequence similarity to Bacillus cereus strain J-1 16S rRNA gene partial sequence with accession number: AY305275 and has been deposited in the database of Genbank.